Pengaruh Harga Briket Dunia, Produksi Briket, Dan Inflasi Terhadap Ekspor Briket Di Pasar Internasional Periode 2017-2022 - Joachim, Timothius; Sri Budhi, Made Kembar (Peneliti.net, 2025)
International trade has become a major pillar in global economic growth, opening up new opportunities and encouraging cooperation between countries. International trade plays an important role in economic growth both directly and indirectly because good economic growth must be supported by international trade, both exports and imports. The purpose of this study was to analyze the effect of briquette production, global briquette prices and inflation on Indonesian briquette exports to the international market. The results of the study showed that Indonesian briquette exports were influenced by 79 percent by briquette prices, production, and inflation, while the remaining 21 percent was influenced by other factors outside the regression model. The results of the analysis showed that world briquette prices, briquette production, and inflation simultaneously influenced briquette exports in the international market for the period 2017-2022. World briquette prices, briquette production, and inflation partially had a positive effect on briquette exports in the international market for the period 2017-2022.